(untitled) (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Premessa: ambiti e obiettivi della ricerca - 2. Il diritto penale nel paradigma dell’ecologia integrale quale espressione del principio della misericordia - 3. La funzione della pena secondo Papa Francesco: i principi generali - 4. La pena di morte e la sua inconciliabilità con il Vangelo - 5. L’ergastolo come “pena di morte nascosta” e la tortura come “peccato mortale” - 6. Conclusioni. The Function of Punishment in the Teachings of Pope Francis ABSTRACT: This article analyses the doctrine about the function of punishment and the criminal justice system in the teachings of Pope Francis. The reflection about punishment is understood in the light of the principles of the Mercy of God and the Integral ecology. The central idea is represented by the concept of reparative justice. Particularly, it will be take in consideration the questions of death penalty, life sentence and torture, and - in the conclusions - a brief comparative analysis with the Italian legal justice system.